Human Cytomegalovirus Infection of Caco-2 Cells Occurs at the Basolateral Membrane and Is Differentiation State Dependent - Jarvis, Michael A. (American Society for Microbiology, 1999)
Epithelial cells are known to be a major target for human cytomegalovirus (HCMV) infection; however, the analysis of virus-cell interactions has been difficult to approach due to the lack of in vitro models. In this study, we established a polarized epithelial cell model using a colon epithelial cell-derived cell line (Caco-2) that is susceptible to HCMV infection at early stages of cellular differentiation. Infection of polarized cells was restricted to the basolateral surface whereas virus was released apically, which was consistent with the apical and not basolateral surface localization of two essential viral glycoproteins, gB and gH. HCMV infection resulted in the development of a cytopathology characteristic of HCMV infection of colon epithelium in vivo, and infection did not spread from cell to cell. The inability of HCMV to infect Caco-2 cells at late stages of differentiation was due to a restriction at the level of viral entry and was consistent with the sequestration of a cellular receptor for HCMV. These observations provide the first evidence that restriction of HCMV replication in epithelial cells is due to a receptor-mediated phenomenon.